2015
DOI: 10.4049/jimmunol.1500668
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B–Mediated Activation-Induced Death of CD4+ T Cells Inhibits Murine Acute Graft-versus-Host Disease

Abstract: Granzyme B (GzmB) has previously been shown to be critical for CD8+ T cell-mediated graft-versus-host disease (GVHD) but dispensable for GVHD mediated by CD4+ T cells. However, previous studies used high doses of CD4+ T cells in MHC-mismatched models that caused rapid and lethal GVHD. Due to the hyperacute lethality, it is possible that the role of GzmB was concealed by the system. Therefore, in this study we have titrated down the T cell dose to precisely determine the contribution of GzmB in GVHD mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…We have found that Spi6 expression is higher in effector T cells than memory T cells, which is consistent with our previous reports showing that GzmB mainly causes AICD in CD8 C and CD4 C effector T cells. 14,15,40 These findings suggest that the GzmB-Spi6 axis may predominantly function during donor-derived effector T cell clonal expansion. In support of this notion, a recent study showed that Spi6 deficiency in CD8 C T cells causes decreased clonal expansion of short-lived effector T cells but do not change long-term memory T cell pool.…”
Section: E1397247-10mentioning
confidence: 91%
See 2 more Smart Citations
“…We have found that Spi6 expression is higher in effector T cells than memory T cells, which is consistent with our previous reports showing that GzmB mainly causes AICD in CD8 C and CD4 C effector T cells. 14,15,40 These findings suggest that the GzmB-Spi6 axis may predominantly function during donor-derived effector T cell clonal expansion. In support of this notion, a recent study showed that Spi6 deficiency in CD8 C T cells causes decreased clonal expansion of short-lived effector T cells but do not change long-term memory T cell pool.…”
Section: E1397247-10mentioning
confidence: 91%
“…Previous reports including ours show that GzmB-mediated AICD affects various types of T cells. 14,15,28 But it is not clear whether such T cells are killed by GzmB leaked from their own granules or delivered from other T cells. Meanwhile, Spi6 has been shown to protect the integrity of cytotoxic granules in T cells and inhibit endogenous GzmB-mediated damage.…”
Section: Spi6 Predominantly Protects T Cells From Gzmb-mediated Fratrmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were sacrificed at days 17, 36, and 66, and large and small intestines were formalin-fixed, sectioned, and stained with H&E. Intestine tissues were examined using a previously established scoring system (2325). Blinded assessments were made for the presence of crypt epithelial cell apoptosis, crypt regeneration, surface erosion, ulceration, lamina propria inflammation, chronic atrophy, chronic crypt branching, chronic endocrine cell excess, chronic Paneth cell excess, epithelioid vacuolization, attenuation, sloughing into the lumen lymphocytic infiltrate and neutrophilic infiltrate.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 months, the chimeric hosts were irradiated with 800 cGy and transplanted with 4×10 6 BM alone or combined with 3×10 6 PanT cells isolated from BALB/c donors. Hosts are then monitored for GVHD and survival as previously described (42, 43). …”
Section: Methodsmentioning
confidence: 99%